Effectiveness of Perfusion index for Predicting Onset of Paediatric Caudal Block under Sevoflurane Anaesthesia (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Introduction: The caudal block is widely used in paediatric day case surgery as a regional anaesthesia technique. Assessing the onset of caudal block can be challenging since paediatric surgeries are typically performed under general anaesthesia. Clinical signs and objective assessments may not provide timely or reliable feedback. The perfusion index (PI) is viewed as an early and efficient indicator for detecting the onset of caudal block.Methodology: This observational study took place at the Department of Anaesthesia and Pain Medicine in Evercare Hospital Dhaka over 12 months after protocol approval. Purposive sampling was used to select 120 individuals, and detailed data were collected using a structured data collection sheet.Results: In this study analyzing caudal anaesthesia, 10 patients (8.3%) were excluded, leaving data from 110 patients for analysis. Results show that Perfusion Index (PI) most promptly confirms the onset of caudal block, followed by loss of Cremasteric Reflex (CR), while Heart Rate (HR) and Mean Blood Pressure (MBP) reductions confirm it later. At 10 minutes, many patients show a ≥100% increase in PI, with similar trends in other parameters. AUC values suggest moderate discriminatory ability for PI increase (0.364) and absent CR time (0.329) compared to HR and MBP. PI and CR slightly outperform HR and MBP in predicting successful caudal block, but parameter selection depends on clinical context and the importance of sensitivity, specificity, PPV, and NPV.Conclusion: Perfusion index (PI) proves to be a reliable and continuous indicator for promptly identifying the initial stages of caudal block in paediatric patients undergoing general anaesthesia.J Bangladesh Coll Phys Surg 2025; 43: 205-211